The impedance of strip dipole - Ільницький, Л. Я. (Problems of Informatization and Control, 2007)
The mathematical relations for inductive and capacitance conductors are known from the theory of electrodynamics. On the basis of these equations the impedance of strip dipole with consant amplitudes of current and edge charges is determined. At the time of changing of currend and charges the impedance has active and reactive components. The active components describes the emissive ability of dipole. Reactive component determines the reactive field near the dipole